DETERMINANTS OF FDI IN BRICS COUNTRIES: PANEL DATA APPROACH - BIYASE, Mduduzi; ROODERICK, September (Studia Universitatis Babeș-Bolyai Oeconomica, 2018)
We empirically investigates the factors that affect Foreign Direct Investment (FDI) inflows in five BRICS countries for the period 1990–2015. We address the selection bias and unobserved heterogeneity by estimating a panel Heckman selection method and attempts to account for both selection and endogeneity within the new two-stage method. After addressing the above mentioned econometric issues, the infrastructure and GDP per capita variables under the new two-stage method remain positive and significantly similar to the coefficient of infrastructure and GDP per capita under the panel Heckman selection model. In addition, the inverse Mills ratio maintain its level of statistical significance, confirming the presence of both sample selection bias and endogeneity. JEL classification: C22; F21; O16